Study of the amino acids of Russell's lisianthus stems, leaves and flowers - Olefirenko, Anna; Kyslychenko, Viktoria (Annals of Mechnikov's Institute, 2024)
Introduction. Amino acids have an immunomodulatory, antidepressant effect, they are components of collagen, reduce the level of triglycerides in the blood, take an active part in the synthesis and assimilation of vitamins, etc. Natural amino acids have a higher physiological activity compared to synthetic analogues, because in plant raw material they are found in complexes that are easily assimilated by the human body and in biologically available concentrations. Therefore, the search for new sources of biologically active compounds of plant origin to obtain pharmacologically active substances that contain a large number of amino acids is of great interest and importance. In this regard, an in-depth study of the amino acid composition of a non-officinal plant - Russell's lisianthus (Lisianthus russellianus Hook.) of the Gentianaceae family (Gentianaceae Juss.), which is widely cultivated around the world as an ornamental plant, is promising. The aim of the research was to study the qualitative composition and quantitative content of amino acids in Russell's lisianthus stems, leaves and flowers. Materials and methods. Russell's lisianthus herb of the Borealis Apricot species harvested in August 2023 in the Kharkiv region (Ukraine) was used for the study. Identification and quantification of amino acids in the studied samples of plant raw material was carried out by ion-exchange liquid column chromatography on an amino acid analyzer AAA T-339M manufactured by "Mikrotech" (Czech Republic), equipped with a recording photocell. This technique is based on post-column derivatization of amino acids with ninhydrin. At the same time, interaction products with a characteristic violet (amino acids, wavelength - 570 nm) or yellow (imino acids, wavelength - 440 nm) color are formed. Results and discussion. 18 amino acids were identified in Russell's lisianthus stems, leaves and flowers by ion-exchange liquid column chromatography. Their profile is uniform in composition: 7 essential amino acids (lysine, threonine, valine, methionine, phenylalanine, isoleucine, and leucine), 3 semi-essential (arginine, tyrosine, histidine) and 8 non-essential (aspartic, glutamic acids and γ-aminobutyric acid, serine, glycine, alanine, proline and cystine). The highest content of the sum of amino acids was determined in Russell’s lisianthus leaves (81.9 mg%), somewhat less in the flowers (66.69 mg%), and the lowest content was observed in the stems (36.27 mg%). In terms of content, glutamic and aspartic acids, alanine, proline, leucine dominate in the studied raw materials; GABA, methionine and cystine are contained in minor amounts. Non-essential amino acids predominated in all studied raw materials, but essential amino acids are of the greatest interest to the human body. Their content in Russell's lisianthus stems is 19.52%, in the leaves - 24.37%, and in the flowers - 26.83% of the total amount of amino acids. Among the essential amino acids, leucine, phenylalanine, lysine, and valine are present in the majority, and valine, isoleucine, and methionine are present in small amounts. Conclusions. As a result of the analysis, 18 amino acids were identified in Russell's lisianthus stems, leaves and flowers, of which 7 are essential, 3 are semi-replaceable, and 8 are replaceable. The identified amino acids in the studied raw materials have the same composition but differ in quantitative content. The total amount of detected amino acids is higher in leaves and flowers, and it is minimal in stems. In terms of content, glutamic and aspartic acids, alanine, proline, leucine dominate in the studied raw materials; GABA, methionine and cystine are contained in minor amounts. Thus, the obtained results indicate the biological value of Russell's lisianthus herb and the presence of a wide spectrum of pharmacological activity associated with a fairly high amino acids content. Keywords: Russell's lisianthus (Lisianthus russellianus Hook.), stems, leaves, flowers, amino acids, qualitative composition, quantitative content.